2023
DOI: 10.3390/su15043484
|View full text |Cite
|
Sign up to set email alerts
|

A Patent Bibliometric Analysis of Carbon Capture, Utilization, and Storage (CCUS) Technology

Abstract: Large amounts of CO2 from human socioeconomic activities threaten environmental sustainability. Moreover, uncontrolled resource use and lack of relevant technology exacerbate this issue. For this reason, carbon capture, utilization, and storage (CCUS) technology has gained worldwide attention. Many scholars have researched CCUS, but few have used CCUS patent bibliometric analysis from a unified perspective. This article aims to provide a conclusive analysis for CCUS researchers and policymakers, as well as sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Furthermore, we determine, through different patent databases, publication dates, applicants, owners, patent classifications, and patent jurisdictions. This type of research has already been demonstrated in various fields through several recent publications on hydrogel-based coatings [9], biocontrol agents [10], bioinks [11], energy [12,13], carbon [14], plant-based vaccines [15], and orthosis [16].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, we determine, through different patent databases, publication dates, applicants, owners, patent classifications, and patent jurisdictions. This type of research has already been demonstrated in various fields through several recent publications on hydrogel-based coatings [9], biocontrol agents [10], bioinks [11], energy [12,13], carbon [14], plant-based vaccines [15], and orthosis [16].…”
Section: Introductionmentioning
confidence: 91%
“…Carbon capture, utilization, and storage (CCUS) technology is considered among the crucial solutions to address carbon emissions. However, the current state of CCUS technology in China appears to have significant room for improvement [54]. Therefore, it is imperative for the relevant departments to bolster their support for research and development in this field.…”
Section: Policy Suggestions and Study's Limitationsmentioning
confidence: 99%
“…• Decarbonization collectively describes measures to reduce the amount of carbon dioxide (CO 2 ) generated in logistics operations and shift towards climate neutrality [96,97]. This trend has a high impact because the problem of high emissions is particularly relevant for logistics [44], which in supply chains accounts for 60% of global emissions [98].…”
Section: Literature Reviewmentioning
confidence: 99%